2002
DOI: 10.1176/jnp.14.3.277
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow Changes Associated With Schneiderian First-Rank Symptoms in Schizophrenia

Abstract: The authors examined the severity of Schneiderian first-rank symptoms in relation to regional cerebral blood flow (rCBF) with the use of PET. Eighty-seven schizophrenic patients were imaged during an eyes-closed condition during which they were instructed to relax and not perform any specific task (random episodic silent thought, or REST). Schneiderian symptoms were rated by using structured assessment instruments. The Schneiderian score of the patients was positively correlated with rCBF in right superior par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(39 citation statements)
references
References 25 publications
5
31
0
3
Order By: Relevance
“…Furthermore, Mohr et al (2006) showed that performance in this OBT-task positively correlated with degree of positive schizotypy as measured by the frequency of spontaneously experienced schizotypal perceptual alterations (perceptual aberration score; PA score; (Chapman et al, 1978)). As high PA scores have been considered an indicator of psychosis-proneness (Chapman et al, 1994;Lenzenweger, 1994;Tallent and Gooding, 1999), these findings would suggest that positive schizotypy (and by inference passivity symptoms in schizophrenia) might also be associated with impaired neural processing at the TPJ, in concordance with findings in patients with schizophrenia (Spence et al, 1997;Franck et al, 2002;Farrer et al, 2004). Yet, due to their limited temporal resolution the abovementioned fMRI and PET studies did not allow to distinguish between strength-related versus duration-related increases in TPJ activation and can thus not assess some of the basic mechanisms of the functional aberrations in schizophrenic patients (Lehmann et al, 2005).…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…Furthermore, Mohr et al (2006) showed that performance in this OBT-task positively correlated with degree of positive schizotypy as measured by the frequency of spontaneously experienced schizotypal perceptual alterations (perceptual aberration score; PA score; (Chapman et al, 1978)). As high PA scores have been considered an indicator of psychosis-proneness (Chapman et al, 1994;Lenzenweger, 1994;Tallent and Gooding, 1999), these findings would suggest that positive schizotypy (and by inference passivity symptoms in schizophrenia) might also be associated with impaired neural processing at the TPJ, in concordance with findings in patients with schizophrenia (Spence et al, 1997;Franck et al, 2002;Farrer et al, 2004). Yet, due to their limited temporal resolution the abovementioned fMRI and PET studies did not allow to distinguish between strength-related versus duration-related increases in TPJ activation and can thus not assess some of the basic mechanisms of the functional aberrations in schizophrenic patients (Lehmann et al, 2005).…”
Section: Introductionsupporting
confidence: 74%
“…These results were replicated using functional magnetic resonance imaging (fMRI) (Ganesan et al, 2005). Franck et al (2002) found a positive correlation between Schneiderian first-rank symptoms of schizophrenia and cerebral blood flow in right parietal cortex, as measured by PET. In a further study, Farrer et al (2004) tested self-other discrimination with PET while healthy subjects and patients with Schneiderian first-rank symptoms of schizophrenia performed arm movements and watched differently distorted images of their arms displayed on a computer screen.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…"voices" whereby inner speech is erroneously attributed to external agents) show abnormal activation of primary auditory areas in their left temporal lobe, as if they were processing an external auditory stimulus [63]. Similarly, an increased activity in the right posterior parietal lobe has been observed in patients with delusion of influence, either at rest [64] or during an action recognition task [31]. Such increased activation could likely be related to the loss of frontal inhibition on the corresponding areas.…”
Section: Conclusion a Neural Hypothesis For Self-recognition And Itsmentioning
confidence: 97%
“…Chez des patients exprimant des symptômes schneideriens (ayant, par exemple, l'impression que leurs mouvements étaient contrôlés de l'extérieur) au moment de l'expé-rience, cette région pariétale était plus fortement activée que chez les sujets témoins ou que chez les mêmes patients en phase de rémission. On peut noter que cette même région pariétale droite est activée au repos chez des patients présentant un score élevé sur l'échelle d'évaluation des symptômes positifs (SAPS) [1], c'est-à-dire présentant ou ayant présenté une symptomatologie schneiderienne [16]. Notons enfin que l'asymétrie anatomique normale entre les deux régions pariétales infé-rieures au profit de la région pariétale gauche est inversée chez le sujet schizophrène, chez lequel la région droite est plus développée [17].…”
Section: Anatomie Fonctionnelle Des Symptômes Schneideriensunclassified